2011
DOI: 10.1186/1465-9921-12-71
|View full text |Cite
|
Sign up to set email alerts
|

Health status in the TORCH study of COPD: treatment efficacy and other determinants of change

Abstract: BackgroundLittle is known about factors that determine health status decline in clinical trials of COPD.ObjectivesTo examine health status changes over 3 years in the TORCH study of salmeterol+fluticasone propionate (SFC) vs. salmeterol alone, fluticasone propionate alone or placebo.MethodsSt George's Respiratory Questionnaire (SGRQ) was administered at baseline then every 6 months.Measurements and Main ResultsData from 4951 patients in 28 countries were available. SFC produced significant improvements over pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
57
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 25 publications
4
57
2
Order By: Relevance
“…A decline in skeletal muscle mass in underweight patients and an increase in FM in overweight and obese patients were independent determinants for clinically significant deterioration in health status over 3 years. The overall change in health status over 3 years was small (mean change 0.84 ± 14.43 points) and comparable with recent results from the TORCH study, where SGRQ total score remained stable and worsened by about 2 points over 3 years in both the treated and the placebo groups [28]. In addition, comparable results were shown in the UPLIFT trial, as the SGRQ total score showed a worsening of about 1 point over 3 years [29].…”
Section: Discussionsupporting
confidence: 70%
“…A decline in skeletal muscle mass in underweight patients and an increase in FM in overweight and obese patients were independent determinants for clinically significant deterioration in health status over 3 years. The overall change in health status over 3 years was small (mean change 0.84 ± 14.43 points) and comparable with recent results from the TORCH study, where SGRQ total score remained stable and worsened by about 2 points over 3 years in both the treated and the placebo groups [28]. In addition, comparable results were shown in the UPLIFT trial, as the SGRQ total score showed a worsening of about 1 point over 3 years [29].…”
Section: Discussionsupporting
confidence: 70%
“…Our observed improvement of 3.2 units in SGRQ-TS at 4 months was similar to the mean reduction of 3.0 units reported in the Toward a Revolution in COPD Health (TORCH) study averaged over 3 years among those receiving salmeterol and fl uticasone. 34,35 Similarly, the Understanding Potential Longterm Impacts on Function with Tiotropium (UPLIFT) study examined the use of tiotropium and demonstrated mean absolute changes in SGRQ-TS ranging from 2.3 to 3.3 units in the treatment arm. 36,37 Although not statistically significant, our between-group difference in SGRQ-TS at 4 months was 2.3 units, similar to the between-group diff erence of 2.7 units in the UPLIFT study.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in another study, significant negative correlation between FEV 1 % pred and the Total score was described in a sample of severe COPD patients ( r =−0.4, P <0.001) 46. In a double-blind placebo-controlled study designed to assess the benefits of the fixed combination inhaler fluticasone propionate and salmeterol versus placebo, the longitudinal analysis of data for 4,951 COPD patients showed significant negative correlation regarding the change in SGRQ scores and FEV 1 during the 3 years of the study in all treatment arms, combined 47. Previously, we also found a significant negative correlation between the Total SGRQ score and FEV 1 % pred 27…”
Section: Discussionmentioning
confidence: 99%